An assessment of services for custodial parents during supervised visitation. Issue 2 (2nd April 2020) - Cefarelli, Normajean
Abstract: Supervised visitation programs provide court-mandated services in cases with purported risks to (a) child(ren), or during custody or visitation disputes. The purpose of this study was to determine if there is a need to provide support services for the custodial and/or foster parent during supervised visitation sessions. The researcher conducted a mixed methods study with a cross-sectional comparative design, using an internet-based simultaneous quantitative and qualitative needs assessment. Participants included custodial/foster parents, and visitation centers staff. Results indicated that custodial/foster parents share experiences of emotional stress, fear for their child(ren)'s safety during visitations, lack of coherence, and changes in the family dynamic. Resources of formal kinship; spouse/partner support; and information, logistical, mental health, and therapeutic support could help custodial/foster parents.